Bookline: a technological tool at service of scientific papers evaluation in academic events - Weyh, Cênio Back; Oliveira, Fernando Luis (Universidade Estadual de Campinas, 2016)
The use of technologies has been more common each day in teaching. The softwares that facilitate the teacher’s work as a technological source can also be used for other aspects of education. The scientific events are fundamental for the particular student’s learnings in higher education. Considering the complexity of coordinating an event due to the number of people involved and the means of sending works for analysis and their evaluation during the event, we looked forward to developing technological tools. In this sense, we developed a software to manage scientific events providing an interface for the organization of the works’ evaluation and of the criteria for evaluation, as well as the management of evaluators and their thematic areas of performance. The software named Bookline was designed for mobile environments, making it possible for the evaluators to wander around freely during the evaluations, getting additional information about each criterion of evaluation, in order to enable the widest spectrum in the constitution of the work’s mark. At the end of the evaluations, the evaluator sends his considerations to the central server, that processes and compiles its data and from the rest of the evaluators identifying if the work was accepted.